Safe Among the Unsafe: Psychological Safety Climate Strength Matters for Team Performance. (August 2023) - Fyhn, Bård; Bang, Henning; Sverdrup, Therese E.; Schei, Vidar
Team psychological safety, as a shared perception, is persistently found to be important for team performance. However, team members may not necessarily agree on the level of safety within the team. What happens when team members have dispersed perceptions of team psychological safety? Through a survey-based study involving 1, 149 members of 160 management teams, we found that, not only is the level of team psychological safety positively related to team performance, but also that sharedness among team members (team psychological safety climate strength) moderates this relationship. The more team members agree on the level of team psychological safety, the stronger the effect of team psychological safety on team performance. Further, having at least one member who perceives the team as psychologically safe may lift team performance in a team of low psychological safety. We discuss theoretical and practical implications of looking beyond average levels of team psychological safety for building high-performing teams.